2021
DOI: 10.1016/j.jpsychires.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on stress, anxiety, and depressive disorders in German primary care: A cross-sectional study

Abstract: Several studies revealed that mental disorders' prevalence increased during the COVID-19 pandemic, particularly in young and female individuals. Such studies represent individuals' subjective perceptions and not the number of mental health cases treated in primary care. Thus, this study aimed to describe the changes in depression, anxiety, and stress disorder diagnoses in General Practitioner (GP) practices during the COVID-19 pandemic. More than three million patients of 757 German GP practices were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
3
29
0
1
Order By: Relevance
“…Due to the influx of hospitalisations related to COVID, healthcare staff have had to work longer hours with limited resources increasing their vulnerability to burnout and stress [ 53 ]. This has, in turn, drastically affected mental health, with reports of heightened anxiety found in frontline healthcare staff across many countries [ 18 , 141 ]. Non-frontline workers also had an increase in anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the influx of hospitalisations related to COVID, healthcare staff have had to work longer hours with limited resources increasing their vulnerability to burnout and stress [ 53 ]. This has, in turn, drastically affected mental health, with reports of heightened anxiety found in frontline healthcare staff across many countries [ 18 , 141 ]. Non-frontline workers also had an increase in anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring different population groups affected by COVID-19 have identified some common risk factors associated with a higher likelihood of developing anxiety symptoms, including: younger age groups, being female, having pre-existing mental health issues, and lower socioeconomic status (SES) populations [ 18 , 19 ]. The effects of COVID-19 on healthcare workers, the general population, and other vulnerable groups such as pregnant women have been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of general and specialized practices in Germany [6]. Finally, this database has already been used in previous studies focusing on SARS-CoV-2 [7][8][9], specifically the psychological consequences of SARS-CoV-2 [10,11]. The "Disease Analyzer" database used for analysis contains anonymized electronic patient records.…”
Section: Databasementioning
confidence: 99%
“…Several studies tried to extrapolate results from previous (health-related) crises as well as first results from the early COVID-19 pandemic to predict further changes of mental health burden ( Fan et al, 2021 ; Santomauro et al, 2021 ). In this context, it was assumed that not only psychopathological symptoms would increase but also the prevalence rates of full-threshold mental disorders ( Bohlken et al, 2021 ; Santomauro et al, 2021 ). For example, based on a systematic review, Santomauro et al (2021) estimated a global increase in anxiety disorders of 76.2 million (25.6 % increase) and an increase in major depressive disorders of 53.2 million (27.6 % increase) due to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Such predictions are prone to imprecision and uncertainty; nevertheless, they highlight the need for assessing psychopathological symptom changes as well as the incidence and persistence of mental disorders during this challenging time. It can be expected that potential changes in the incidence of full-threshold mental disorders only become evident in the longer run with a distinct delay ( Bohlken et al, 2021 ), which again emphasizes the need for ongoing assessments.…”
Section: Introductionmentioning
confidence: 99%